Dissection of early transcriptional responses to water stress in Arundo donax L. by unigene-based RNA-seq. Issue 1 (December 2016) - Fu, Yuan; Poli, Michele; Sablok, Gaurav; Wang, Bo; Liang, Yanchun; Porta, Nicola; Velikova, Violeta; Loreto, Francesco; Li, Mingai; Varotto, Claudio
Abstract Background Arundo donax L. (Poaceae) is considered one of the most promising energy crops in the Mediterranean region because of its high biomass yield and low input requirements, but to date no information on its transcriptional responses to water stress is available. Results We obtained by Illumina-based RNA-seq the whole root and shoot transcriptomes of youngA. donax plants subjected to osmotic/water stress with 10 and 20 % polyethylene glycol (PEG; 3 biological replicates/organ/condition corresponding to 18 RNA-Seq libraries), and identified a total of 3034 differentially expressed genes. Blast-based mining of stress-related genes indicated the higher responsivity of roots compared to shoots at the early stages of water stress especially under the milder PEG treatment, with a majority of genes responsive to salt, oxidative, and dehydration stress. Analysis of gene ontology terms underlined the qualitatively different responses between root and shoot tissues. Among the most significantly enriched metabolic pathways identified using a Fisher's exact test with FDR correction, a crucial role was played in both shoots and roots by genes involved in the signaling cascade of abscisic acid. We further identified relatively large organ-specific differences in the patterns of drought-related transcription factor AP2-EREBP, AUX/IAA, MYB, bZIP, C2 H2, and GRAS families, which may underlie the transcriptional reprogramming differences between organs. Through comparative analyses with major Poaceae species based on Blast, we finally identified a set of 53 orthologs that can be considered as a core of evolutionary conserved genes important to mediate water stress responses in the family. Conclusions This study provides the first characterization ofA. donax transcriptome in response to water stress, thus shedding novel light at the molecular level on the mechanisms of stress response and adaptation in this emerging bioenergy species. The inventory of early-responsive genes to water stress identified could constitute useful markers of the physiological status ofA. donax and be a basis for the improvement of its productivity under water limitation. The full water-stressedA. donax transcriptome is available for Blast-based homology searches through a dedicated web server (http://ecogenomics.fmach.it/arundo/ ).